Faktor-Faktor yang Mempengaruhi Kepuasan Pelajar SMA terhadap Penggunaan Produk Asuransi Kecelakaan Diri PT Takaful Keluarga Medan: - Desi Rahmawati Supraja; Tri Inda Fadhila Rahma; Nursantri Yanti (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Personal accident insurance is protection against all risks of a person resulting in death and accidents to a person. This study aims to determine what factors affect the satisfaction of high school students whose one school is located in North Sumatra towards the use of personal accident insurance products at PT. Takaful Keluarga Medan. The method used in this study is a quantitative method. The population of this study was conducted on students in one of the senior high schools in North Sumatra with a sample finding of 71 students. Using primary data by distributing questionnaires and multiple regression analysis methods using hypothesis testing. The results of this study simultaneously from the variables of product quality, price, and service quality have a significant effect on customer satisfaction (high shcool stidents). Then partially the product quality variable also has an effect on customer satisfaction and the price variable itself has a significant effect on customer satisfaction and the quality variable has no significant positive effect on customer satisfaction (high school students). Keywords: Personal accident insurance, price, service quality, product quality.